Produção de bulbos e de sementes de cebola no norte de Minas Gerais - Érica Lima Araújo (2022)
The onion (Allium cepa L.) is a biennial crop, having a vegetative phase that ends with the formation of a bulb in the first year and in the second year there are cultivars that need a cold period for the change from the vegetative to the reproductive phase to occur ranges from flowering to seed production. In places where the winter temperature is not naturally low to stimulate flowering, it is necessary that the bulbs are submitted to an artificial vernalization (refrigeration), with temperatures of 5° to 10° C for 60 to 90 days. In the north of Minas Gerais, information on the production of onion seeds and bulbs is scarce. Thus, the objective of this work was to evaluate the production and quality of bulbs and seeds of five onion varieties. The experiment was carried out at the Federal University of Minas Gerais, Montes Claros Campus, in the two phases of the crop: vegetative phase in 2020 and reproductive phase in 2021. Five onion varieties were used, Alfa Tropical, BRS Alfa São Francisco, BRS 367, BRS Sustare and IPA 11. The experimental design was complete randomized blocks with five replications. Data were submitted to normality and homogeneity tests, and subsequently submitted to analysis of variance using the F test, with means compared using the t test (p<0.05). The bulbs harvested in the first phase were evaluated, selected and subjected to artificial vernalization at 5° C for 90 days in a cold chamber, before being planted to obtain the seeds. The following characteristics of the vegetative phase were evaluated, fresh mass, dry mass of bulbs, percentage of commercial bulbs, bulb productivity. The characteristics evaluated in the reproductive phase were number of umbels per plot, moisture, fresh mass, dry mass of seeds, first germination count, germination speed index, weight of one thousand germination seeds, dry mass of seedlings, weight of one thousand seeds emergence, emergence, first emergency count, emergence speed index, seedling dry mass at emergence and seed yield. The varieties showed a productivity of bulbs that varied from 100.87 to 72.96 t ha-1 and in relation to seed yield, cultivar IPA 11 showed an increase of 62.8% in relation to variety BRS 367. For the number of umbels, the IPA 11 variety had a 26.5% increase in relation to BRS 367. Thus, the evaluated varieties showed productive performance in the edaphoclimatic conditions of Montes Claros, demonstrating that the region has great potential not only for the production of bulbs, but also for onion seed production.